O tutor presencial de cursos superiores a distância: atribuições, formação e status profissional - Souza, Roberta de Moraes Jesus de (2010)
The goal of this dissertation was to discuss the functions attributed to the presential tutor of Distance Education (DE) graduation courses and analyze the formation and the status of this profession. In the initial chapters, the historical context is presented which features the contemporary project DE, especially in relation to globalization, to the development of information and communication technologies and to neoliberalism and the functions attributed to the presential tutor in studies about DE and legislation. The theoretic referential of the study was based on Belloni (2009), Leal (2003), Libâneo (2010), Maués (2009), O'Rourke (2003), Pretto (2001), Romão (2008), Santos (2007), Schulman (2005) and Toschi (2004), and others. The research, qualitative type, consisted on interviews with the seven presential tutors who worked, at the first 2010 term, at UNOPAR (North Paraná University), pole Rio Verde, Goiás. The studies which mention the presential tutor attributions and legislation show that functions of cognitive, affective and direction nature, which are similar to teachers knowledges, such as are shown by field researches on teacher formation. The analysis show vague and inaccurate attribution in relation to this professional, absence of specific formation and precarious professional statute.